2015
DOI: 10.1177/1753465815589904
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of emphysema using bronchoscopic lung volume reduction coil technology: an update on efficacy and safety

Abstract: Abstract:In the last decade several promising bronchoscopic lung volume reduction (BLVR) treatments were developed and investigated. One of these treatments is BLVR treatment with coils. The advantage of this specific treatment is that it works independently of collateral flow, and also shows promise for patients with a more homogeneous emphysema disease distribution. Seven years ago, the very first patients were treated with BLVR coil treatment and currently large randomized, controlled trials are underway. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 18 publications
(71 reference statements)
1
8
0
Order By: Relevance
“…The SGQR response at 90 days after final treatment was greater than in the usual care group and > 60% of the patients in BVR group experienced improvement in FEV 1 and no significant adverse event was reported. It is also confirmed that BVR using coils are safe and with no late pneumothoraces, coil migration or unexpected adverse events by Hartman et al [19]. According to this study, 3 [16][17][18][19][20] years after treatment 50% of the patients maintained an improvement 6MWT, SGRQ and dyspnea scores.…”
Section: Coilssupporting
confidence: 86%
“…The SGQR response at 90 days after final treatment was greater than in the usual care group and > 60% of the patients in BVR group experienced improvement in FEV 1 and no significant adverse event was reported. It is also confirmed that BVR using coils are safe and with no late pneumothoraces, coil migration or unexpected adverse events by Hartman et al [19]. According to this study, 3 [16][17][18][19][20] years after treatment 50% of the patients maintained an improvement 6MWT, SGRQ and dyspnea scores.…”
Section: Coilssupporting
confidence: 86%
“…To put the cost of the EBV treatment in perspective, we compared the costs‐effectiveness analyses of other treatments for advanced emphysema patients such as lung volume reduction coil treatment, LVRS and lung transplantation. Another bronchoscopic lung volume reduction treatment option is the treatment with coils . The REVOLENS trial investigated the lung volume reduction coil treatment and reported an ICER of $782 598 (approximately €738 400) per additional QALY, calculated over a 1‐year period .…”
Section: Discussionmentioning
confidence: 99%
“…Coils are a potential treatment option for patients who do not qualify for endobronchial valve treatment [due to for example positive interlobar collateral ventilation status (16)] or lung volume reduction surgery, and can also be offered as a bridge to lung transplantation. Selecting optimally treated, symptomatic COPD patients with emphysema and severe hyperinflation (absolute minimal criteria for hyperinflation: RV >200% predicted and RV/TLC ratio >58%, measured using body plethysmography), while avoiding significant airway disease such as asthma, chronic bronchitis and bronchiectasis, is key to achieve treatment success (12,28,29). Additional patient inclusion and exclusion criteria specific for the coil treatment from our center are summarized in Table 3.…”
Section: Patient Selection Criteriamentioning
confidence: 99%